Analisis Penyelesaian Masalah Numerasi Matematika Berdasarkan Teori APOS di Kelas V SD - Alicia Ozika, Purwa; Maruti, Endang Sri; Rulviana, Vivi (Universitas Nurul Jadid, 2025)
This research aims to describe and explain students' mistakes in solving mathematical numeracy problems based on APOS theory in fifth grade elementary school. This research method uses qualitative descriptive research. The research instruments used observation sheets, test question sheets and interviews. According to the research results, students' understanding of fraction material is quite high, although there are some students who actually understand the material but are lazy in taking the tests given so they only do a few questions but are not thorough enough and are too hasty in understanding the material and working on the questions. Errors at the action stage are included in the low category, because the majority of students can already understand what is known in the question. Errors at the process stage are included in the low category, because most students already understand what is asked in the question. At the error object stage in implementing the plan, students are not yet fully able to solve the problem, there are still many students who only write down the formula and there are also those who carry out calculation operations but the final result is wrong. Error at schema stage. At this stage, it is included in the highest category, because students do not write conclusions from the final results of the questions in question and students do not check their answers again.